EFEKTIVITAS ESTER SORBITAN UNTUK STABILISASI SARI BUAH - Anny Sulaswatti; Siti Isnijah; Hilyati Hilyati; Nuryatini Nuryatini; M Greasia; R Endang; Haryadi Haryadi; Burhanuddin Burhanuddin (Jurnal Kimia Terapan Indonesia, 1999)
Sorbitan esters is a nonionic surfactant which can be used as stabilizer or emulsifer i.e for food products. Nonionic surfactant is almost completely provided imported.Fatty acid derived from vegetable oil are potential for producing these esters. Indonesia is one of the largest palm oil producers in the world and sorbitol has already be produced in Indonesia, so that is has oppotnity to develop sorbitan ester. The aim this research is to evaluate the application of P3KT sorbitan esters as stabilizer in fruit juicescomparing with available commerical food stabilize.